2018
DOI: 10.1038/s41592-018-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

StaPLs: versatile genetically encoded modules for engineering drug-inducible proteins

Abstract: Robust approaches for chemogenetic control of protein function would have many biological applications. We developed stabilizable polypeptide linkages (StaPLs) based on hepatitis C virus protease. StaPLs undergo autoproteolysis to cleave proteins by default, whereas protease inhibitors prevent cleavage and preserve protein function. We created StaPLs responsive to different clinically approved drugs to bidirectionally control transcription with zinc-finger-based effectors, and used StaPLs to create single-chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Using this system, they demonstrated dose-dependent transcription activation, but the system was irreversible. 88 In a similar approach, Tague et al used the NS3 protease domain and its inhibitor BILN-2061 as a ligand-inducible connection (LInC) to control the association of DNA binding and transcription activation domains. In their design, the viral protease was incorporated into dCas9-VPR such that the protease was positioned between the DNA binding sca ffold and the C-terminal region that contained a nuclear localization sequence (NLS) and the VPR transcription activation domain (dCas9-NS3-NLS-VPR).…”
Section: Control By Small-molecule Activatorsmentioning
confidence: 99%
“…Using this system, they demonstrated dose-dependent transcription activation, but the system was irreversible. 88 In a similar approach, Tague et al used the NS3 protease domain and its inhibitor BILN-2061 as a ligand-inducible connection (LInC) to control the association of DNA binding and transcription activation domains. In their design, the viral protease was incorporated into dCas9-VPR such that the protease was positioned between the DNA binding sca ffold and the C-terminal region that contained a nuclear localization sequence (NLS) and the VPR transcription activation domain (dCas9-NS3-NLS-VPR).…”
Section: Control By Small-molecule Activatorsmentioning
confidence: 99%
“…The availability of ANR to basally localize a protein activity fused to NS3a away from a site of action, or to act as an intramolecular regulatory switch, provides an appealing option for reducing background, but protease-based NS3a control systems offer the possibility of obtaining the complete absence of a protein activity in the cell prior to the addition of a small molecule input. 10,11,27,42 However, the reduced background that can be obtained with protease-based systems comes at the expense of speed, as protein accumulation is required for activation. Furthermore, we have found that catalytically-dead NS3a is an equally effective component of PROCISiR as the active protease, which is advantageous for applications in which off-target proteolytic activity may be a concern.…”
Section: Discussionmentioning
confidence: 99%
“…small molecule assisted shutoff or SMASh-tag; 78 ] could be useful for chasing old and new histones in parallel. Specifically, it will be interesting to determine if recently described orthogonal SMASh-tags [called stabilizable polypeptide linkers or StaPLs; 79 ] could be applied to studying histone dynamics. For example, by tagging two alleles of H3F3B with orthogonal StaPLs and epitope tags, it might be possible to distinguish old H3.3 (degron inhibited before switch and activated after switch) from new H3.3 (degron activated before switch and inhibited after switch).…”
Section: Discussionmentioning
confidence: 99%